Association between gut microbiota and glioblastoma: a Mendelian randomization study - Wang, Song; Yin, Fangxu; Guo, Zheng; Li, Rui; Sun, Wei; Wang, Yuchao; Geng, Yichen; Sun, Chao; Sun, Daqing (Frontiers in Genetics, 2024)
Background: Glioblastoma (GBM) is the most prevalent malignant brain tumor, significantly impacting the physical and mental wellbeing of patients. Several studies have demonstrated a close association between gut microbiota and the development of GBM. In this investigation, Mendelian randomization (MR) was employed to rigorously evaluate the potential causal relationship between gut microbiota and GBM. Methods: We utilized summary statistics derived from genome-wide association studies (GWAS) encompassing 211 gut microbiota and GBM. The causal association between gut microbiota and GBM was scrutinized using Inverse Variance Weighted (IVW), MR-Egger, and Weighted Median (WM) methods. Cochrane’s Q statistic was employed to conduct a heterogeneity test. MR-Pleiotropic Residuals and Outliers (MR-PRESSO) were applied to identify and eliminate SNPs with horizontal pleiotropic outliers. Additionally, Reverse MR was employed to assess the causal relationship between GBM and pertinent gut microbiota. Results: The MR study estimates suggest that the nine gut microbiota remain stable, considering heterogeneity and sensitivity methods. Among these, the family.Peptostreptococcaceae and genus.Eubacterium brachy group were associated with an increased risk of GBM, whereas family.Ruminococcaceae, genus.Anaerostipes, genus.Faecalibacterium, genus.LachnospiraceaeUCG004, genus.Phascolarctobacterium, genus.Prevotella7, and genus.Streptococcus were associated with a reduced risk of GBM. Following Benjamini and Hochberg (BH) correction, family.Ruminococcaceae (OR = 0.04, 95% CI: 0.01–0.19, FDR = 0.003) was identified as playing a protective role against GBM. Conclusion: This groundbreaking study is the first to demonstrate that family.Ruminococcaceae is significantly associated with a reduced risk of GBM. The modulation of family_Ruminococcaceae for the treatment of GBM holds considerable potential clinical significance.